2013
DOI: 10.1101/cshperspect.a013169
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress Sensing in the Unfolded Protein Response

Abstract: Secretory and transmembrane proteins enter the endoplasmic reticulum (ER) as unfolded proteins and exit as either folded proteins in transit to their target organelles or as misfolded proteins targeted for degradation. The unfolded protein response (UPR) maintains the protein-folding homeostasis within the ER, ensuring that the protein-folding capacity of the ER meets the load of client proteins. Activation of the UPR depends on three ER stress sensor proteins, Ire1, PERK, and ATF6. Although the consequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
620
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 663 publications
(635 citation statements)
references
References 77 publications
12
620
0
3
Order By: Relevance
“…Three major signalling pathways separately initiated by ER transmembrane sensor proteins, including IRE1, PERK and ATF6, are involved in ER stress [43]. We subsequently knocked down Ire1, Perk and Atf6 with siRNAs in stearicacid-treated INS-1 cells, and found that inhibition of Ire1 and Atf6 failed to inhibit stearic-acid-induced stimulation of miR-34a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Three major signalling pathways separately initiated by ER transmembrane sensor proteins, including IRE1, PERK and ATF6, are involved in ER stress [43]. We subsequently knocked down Ire1, Perk and Atf6 with siRNAs in stearicacid-treated INS-1 cells, and found that inhibition of Ire1 and Atf6 failed to inhibit stearic-acid-induced stimulation of miR-34a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…uORF translation can also result in activation of the mRNA decay pathways, thus adding another layer to the mechanisms in which uORFs can negatively regulate downstream translation (82). For example, CHOP was identified as a target of the nonsense-mediated mRNA decay pathway that recognizes the presence of a premature termination codon (83).…”
Section: Other Complexities Of Gene Expression Regulated By Uorfsmentioning
confidence: 99%
“…ER stress leads to activation of the unfolded protein response (UPR), a complex signaling network that aims to resolve ER stress and restore ER homeostasis (11,12). Inositol-requiring enzyme 1 (IRE1) is one of the three master modulators of UPR signaling.…”
mentioning
confidence: 99%